1994
DOI: 10.1002/path.1711720204
|View full text |Cite
|
Sign up to set email alerts
|

L‐CAM expression in lymph node and liver metastases of colorectal carcinomas

Abstract: L-CAM, also known as E-cadherin, is a cell adhesion molecule expressed on the plasma membranes of epithelial cells at the intercellular interface. From in vitro gene transfection experiments the idea has been conceived that loss of L-CAM expression might be related to the invasive capacity as well as metastatic potential of tumour cells. In several tumours a relation between the grade of differentiation and L-CAM expression has been noticed: loss of differentiation appears to be associated with loss of L-CAM i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
3

Year Published

1995
1995
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 13 publications
2
9
0
3
Order By: Relevance
“…As the molecule has to be present at the cell surface to permit homotypic adhesion, cytoplasmic E-cadherin is by definition nonfunctional. Abnormal staining patterns (negative, heterogeneous or cytoplasmic only) were seen frequently in adenomas as well as adenocarcinomas of the large bowel, as previously shown [4,11,17,31,32]. As in other human tumours the abnormal E-cadherin staining pattern is likely to reflect reductions or loss of E-cadherin-mediated adhesion.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…As the molecule has to be present at the cell surface to permit homotypic adhesion, cytoplasmic E-cadherin is by definition nonfunctional. Abnormal staining patterns (negative, heterogeneous or cytoplasmic only) were seen frequently in adenomas as well as adenocarcinomas of the large bowel, as previously shown [4,11,17,31,32]. As in other human tumours the abnormal E-cadherin staining pattern is likely to reflect reductions or loss of E-cadherin-mediated adhesion.…”
Section: Discussionsupporting
confidence: 52%
“…Transfection of E-cadherin cDNA into a poorly differentiated human colon carcinoma cell line increases cell polarity and intercellular cohesion, and inhibits invasion in vitro [ 12] A number of clinico-pathological studies have demonstrated that loss of E-cadherin expression is commonly associated with high grade and advanced stage in a variety of malignancies including breast carcinoma, prostatic adenocarcinoma, bladder tumours and squamous carcinoma of the head and neck [20,30]. In colorectal cancer, however, alterations in Ecadherin expression have not been found to correlate with its metastatic potential consistently [4,11,17,31,32]. However, in previous studies no paired samples of liver metastases and corresponding primary tumours from the same patient were examined nor were correlations with prognosis and recurrence rate examined.…”
Section: Introductionmentioning
confidence: 99%
“…1 Irregular expression of E-cadherin on the cell surface, presumably causing dysfunction of reflect the situation in the primary tumor, 16 whereas others have found expression of E-cadherin in lymph node metastases from primary sites that lack expression. 9 No correlation between a loss of membranous E-cadherin immunoreactivity and the invasive and metastatic potential of carcinomas has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…A ausência de expressão das E-caderinas parece ser um pré-requisito para promoção da disseminação das células neoplásicas e pode ocorrer por uma diminuição transitória na expressão da molécula durante o início do processo de desenvolvimento da mestástase ou pela emergência de clones celulares em neoplasias primárias com modificações genéticas causando uma diminuição na expressão dessa proteína (Van der Wurff et al 1994, Kashiwagi et al 2010. Este fato foi observado nesta pesquisa na qual a média de expressão de E-caderina foi menor no tumor primário comparado-se ao foco de metástase.…”
Section: Discussionunclassified